Effect of microwave pre-treatment for hydrodistillation extraction on essential oil yield from indigenous herb, Physalis Minima Linn: article - Uda, Nor Fatimah; Che Radzi, NurHaslina (2019)
Extraction of essential oil is a common process used to extract the phytochemical content from the plant that have beneficial impact health. Physalis Minima Linn is a medicinal plant that contains phytochemical that may beneficial to human. Hydrodistillation extraction technique has been used for extraction of oil from this plant by manipulating several parameter. As the objective of this study is to identify the phytochemical contains in the plant and to study the parameter that can affected the yield of extraction, three parameters had been varies which are extraction time ( 30min to 150min), pre-treatment power (180W to 540W) and pretreatment time (30s to 120s). As the result from GC-MS analysis of phytochemical contains, it show that this plant contains aristolene, ibuprofen diethyl phthalate and cyclononasiloxane, octadecamethyl. Each of the phytochemical inhibits the nutritional value to human. The highest yield for this study is about 27.6% which parameter is effect of pretreatment power at 540W while the lowest 4% at 30 minutes extraction time. Each parameter showed the trend that indicate the increasing of extraction yield. From GC-MS, four compound has been identified which are aristolene, ibuprofen, diethyl phthalate and octadecamethyl cyclononasiloxane.